Exploring the Global and the Local in Engineering and International Development: Towards a Liquid Engineering Approach. (29th January 2020) - Robbins, Peter; Wield, David; Wilson, Gordon
Abstract: This special issue on the global and the local in engineering and development builds on an earlier JID Policy Arena on reflexive engineering. It extends our thinking by elaborating the notion of 'liquid engineering', which sees engineering and development as messy and improvisational, a borderland hybrid space, composed of objects and practices, and as reflexive and evolutionary. A set of research articles explore this in different ways using a set of case studies, and the policy arena that follows examines liquid engineering in the context of development practice. All the articles suggest that development engineering is at its most successful when embedded locally and informed by global standards flexed or adapted to local conditions. The local through the integration of relevant case studies can then also shape global practices in useful ways. © 2020 John Wiley & Sons, Ltd.